The Role of Human Factors in Emergency Management: A Malaysian Company Perspective - F Hussin, M; S, Khairilmizal; Hawa B., Siti; Ihsan Mohd Yassin, Ahmad; Husna K., Ainul; Khairul Mohd Salleh, Mohd; Huzaimy Jusoh, Mohamad; Asari Sulaiman, Ahmad; Saadun, Jamil (International Journal of Engineering and Technology, 2018)
Effective emergency management aims to minimize loss during real emergency or disaster.Â For that reason, Public Listed Oil and Gas (PLONG) companies have conducted numerous emergency response exercise (ERE) to evaluate their capability in handling emergency situations, but challenges in PLONG ERE reports obtained did not clearly identify nor categorized challenges based on emergency management effectiveness. With the objective of identifying challenges and influence of human factors based on elements of emergency management effectiveness, documents were analysed towards PLONG ERE reports in 2015. Results were then discussed and validated by experts where it was found that challenges were identified in each element of emergency management and the number of challenges increases with the increasing Tiers of ERE. Trends were also found at each Tier of ERE indicating that the human factors in each element of effective emergency management where 46% of the challenges are organization structures. It is believed that more detailed studies could be contributed to the understanding and further analyse the role of human factors towards effective emergency management..Â Â